(untitled) (TSUL LEGAL REPORT, 2026)
The article analyzes practical issues in establishing effective governance and a healthy competitive environment in the development of road-transport infrastructure in Uzbekistan. It demonstrates that the merging of regulatory and operational functions, along with privileges granted to certain entities, leads to conflicts of interest and inequality. Specifically, the Road Committee serves as both customer and contractor, and government agencies are permitted to sign direct contracts with their affiliated organizations without tenders. The legislative framework is examined, and legal recommendations to improve competition are proposed. The article provides a comprehensive analysis of effective anti-corruption measures in the transport and road infrastructure sector. The study highlights corruption-related risks in this field and their negative impact on economic development and social stability. The research examines the current legal framework in Uzbekistan, focusing on ensuring transparency in tender processes, preventing conflicts of interest, and strengthening accountability mechanisms. In addition, international practices, including those of the World Bank, OECD, European countries, and the United States, are analyzed to explore the potential for adapting these experiences to national legislation. The paper emphasizes modern approaches to combating corruption, such as the introduction of digital technologies, the establishment of open data platforms, and the improvement of monitoring and liability systems. The findings aim to promote transparency and competition in the sector, enhance the efficiency of public spending, and improve the investment climate. This study is of significant theoretical and practical value and can serve as a scientific basis for improving the national anti-corruption strategy in the field of transport infrastructure.